A hydrogen-bonded organic framework based on redox-active tri(dithiolylidene)cyclohexanetrione. Issue 9 (7th January 2021) - Shivakumar, Kilingaru I.; Noro, Shin-ichiro; Yamaguchi, Yuna; Ishigaki, Yusuke; Saeki, Akinori; Takahashi, Kiyonori; Nakamura, Takayoshi; Hisaki, Ichiro
Abstract : The porous architecture derived from a tri(dithiolylidene)cyclohexanetrione derivative reveals the crucial role of bite angle ( θ ) in designing the hydrogen-bonded organic frameworks (HOFs). Abstract : Redox-active hexakis(4-carboxyphenyl) tri(dithiolylidene)cyclohexanetrione (CPDC) was synthesized. The CPDC-based porous framework, constructed via anomalistic helical hydrogen-bonding, exhibites permanent porosity and photoconductivity.